Psikoedukasi “SOBER X Teen” dalam Mengontrol Perilaku Cybersex pada Siswa SMP - Ananda Sri Rahayu; Alifia Putri Fadilah Sati; Anisa Resa Savitri; Erfi Amanda; Imelda Evani; Rafly Rafly; Sakinatun Hasanah; Syerli Akhla Rosa; Ulfa Dwina (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This research aims to determine the effect of SOBER X Teen psychoeducation in controlling cybersex behavior among adolescents The research design is a one group pretest and posttest design The subjects consisted of 68 8th grade junior high school students aged 13-15 years, both male and female The measurement tool used was the cybersex scale Data analysis was conducted using paired sample t-test to observe the differences in cybersex behavior before and after receiving psychoeducation The research results indicate that the p-value = 0000, which is less than 005, meaning that there is an influence of SOBER X Teen psychoeducation on adolescents' understanding of cybersex The implication of this study is that SOBER X Teen psychoeducation can be used as a method to control cybersex behavior in adolescents.